PAX6, brain structure and function in human adults: advanced MRI in aniridia. Issue 5 (12th April 2016) - Yogarajah, Mahinda; Matarin, Mar; Vollmar, Christian; Thompson, Pamela J.; Duncan, John S.; Symms, Mark; Moore, Anthony T.; Liu, Joan; Thom, Maria; van Heyningen, Veronica; Sisodiya, Sanjay M.
Abstract: Objective: PAX6 is a pleiotropic transcription factor essential for the development of several tissues including the eyes, central nervous system, and some endocrine glands. Recently it has also been shown to be important for the maintenance and functioning of corneal and pancreatic tissues in adults. We hypothesized that PAX6 is important for the maintenance of brain integrity in humans, and that adult heterozygotes may have abnormalities of cortical patterning analogous to those found in mouse models. Methods: We used advanced magnetic resonance imaging techniques, including surface‐based morphometry and region‐of‐interest analysis in adult humans heterozygously mutated for PAX6 mutations ( n = 19 subjects and n = 21 controls). Using immunohistochemistry, we also studied PAX6 expression in the adult brain tissue of healthy subjects ( n = 4) and patients with epilepsy ( n = 42), some of whom had focal injuries due to intracranial electrode track placement ( n = 17). Results: There were significant reductions in frontoparietal cortical area after correcting for age and intracranial volume. A greater decline in thickness of the frontoparietal cortex with age, in subjects with PAX6 mutations compared to controls, correlated with age‐corrected, accelerated decline in working memory. These results also demonstrate genotypic effects: those subjects with the most severe genotypes have the most widespread differences compared with controls. We also demonstrated significant increases in PAX6‐expressing cells in response to acute injury in the adult human brain. Interpretation: These findings suggest a role for PAX6 in the maintenance and consequent functioning of the adult brain, homologous to that found in other tissues. This has significant implications for the understanding and treatment of neurodegenerative diseases.